Oscillations damping and stability improvement of solar photo-voltaic cell and battery energy storage system connected to a D.C. microgrid using metaheuristic optimized PID controller / Mohamed M.H. Adam ... [et al.] - Adam, Mohamed M.H.; Naeem, Ameer; Hidayat, Muhamad Nabil; Mohamed Shariff, Noor Fadzilah; Hannoon, Naeem; Varadarajan, Vijayakumar (UiTM Press, 2023)
DC micro-grid is most preferred now a day for Renewable energy sources such as solar, wind, and bio-diesel to share electrical power. At large, a solar photovoltaic (PV) electric power production is supported by a battery energy storage system (BESS) for continuous and reliability of power supply to the loads. To extract maximum power from the solar or wind renewable source, Maximum Power Point Tracking (MPPT) with dc-to-dc voltage control plays a vital role. In this paper, early synchronizing and MPPT of solar power to the grid and better active power transfer capability is analyzed. For this, Met heuristic Optimization based Proportional Integral and Derivative (MOPID) controllers like Whale Optimization Algorithm (WOA) and Grey-Wolf Optimization (GWO) algorithms are compared to show the effectiveness of the operation. These controllers are used in the control scheme of the solar MPPT dc-dc converter operation have better damping and power transferrable capability with earlier settling time and overshoot compared to a system without a controller. The performance of the system is verified through MATLAB/ Simulink simple dc-microgrid environment